Non-vitamin K oral anticoagulant in the prevention and treatment of venous thromboembolism. Why betrixaban is different? - Łukasz Wołowiec; Daniel Rogowicz; Krystian Kałużny; Anna Kałużna; Walery Zukow (Kazimierz Wielki University, 2017)
Venous thromboembolism (VTE) is a disease that includes both deep vein thrombosis (DVT) and pulmonary embolism (PE), is an important cause of morbidity and mortality worldwide. VTE is the third most common cardiovascular illness after acute coronary syndrome and stroke. Unfractionated heparin, low-molecular-weight heparin, and warfarin have been the foundation of venous thromboembolism (VTE) prevention and treatment but are being replaced step-by-step by recently approved non-vitamin K antagonist oral anticoagulants (NOACs). Betrixaban is a direct FXa inhibitor with clear pharmacological characteristics: minimal renal clearance, minimal hepatic metabolism, and long half-life. FDA and Portola Pharmaceuticals on June 23 announced the approval of betrixaban to reduce the risk of venous thromboembolism (VTE) in adults hospitalized for an acute medical illness who have restricted mobility or other risk factors for thromboembolic complications. FDA stated that it approved the drug on the basis of data from the Acute Medically Ill VTE Prevention With Extended Duration Betrixaban (APEX) trial. The APEX trial compared thromboembolic event and death rates in acutely ill patients treated with betrixaban capsules for 35-42 days or subcutaneously administered enoxaparin for 6-14 days. All study participants had been hospitalized for heart failure, respiratory failure, infection without septic shock, rheumatic disorders, or ischemic stroke. Among hospitalized medically ill patients, extended-duration betrixaban demonstrates a favorable net clinical outcome and is associated with an ≈ 30% reduction in fatal or irreversible ischemic or bleeding events compared with standard-duration enoxaparin followed by placebo.